Evaluation of the efficacy of polymeric antigen BLSOmp31 formulated in a new cage-like particle adjuvant (ISPA) administered by parenteral or mucosal routes against Brucella ovis in BALB/c mice. (July 2022) - Moran, María Celeste; Dominguez, María Paula; Bence, Angel Ricardo; Rodriguez, Marcelo Gastón; Goldbaum, Fernando Alberto; Zylberman, Vanesa; Paola, Pardo Romina; Lupi, Giuliana; Marcipar, Ivan Sergio; Lützelschwab, Claudia María; Estein, Silvia Marcela
Abstract: Brucella ovis is an economically important cause of epididymitis in rams worldwide. Polymeric BLSOmp31 was previously identified as a protective immunogen against this pathogen. In this study, BLSOmp31 was formulated with a modified version of ISCOMATRIX adjuvant called ISPA (BLSOmp31/ISPA) and was administered in BALB/C by the subcutaneous and ocular route. The systemic and mucosal immune responses, the opsonic activity of antibodies and the protection conferred against B. ovis were evaluated. BLSOmp31+ISPA injected subcutaneously or by ocular route induced significantly higher IgG antibody levels with a mixed Th1/Th2 profile compared to non-immunized mice. IgA and IgG were detected in sera and nasal, tracheobronchial, vaginal secretions, tears and faeces, from SC immunized mice while in the group immunized by the ocular route a slight increase in both isotypes was mainly observed in all secretions, except in vaginal fluid. Opsonic antibodies stimulated binding and increased uptake of PHrodo™ Green-labelled B. ovis by neutrophils and monocytes. BLSOmp31 administered subcutaneously induced the highest levels of IFN-ɣ. The ocular immunization not only produced significant levels of this cytokine but also IL-4 compared to non-immunized mice. Both, subcutaneous and ocular routes of immunization, significantly protected against B. ovis infection. These results indicate that BLSOmp31/ISPA administered parenterally or by ocular route is a safe and effective vaccine against B. ovis in the murine model. Highlights: BLSOmp31/ISPA was administered by subcutaneous or ocular routes in BALB/c mice. IgA and IgG specific antibodies were detected in sera and in different secretions. Opsonic antibodies stimulated binding and increased uptake of pHrodo™ green-labelled Brucella ovis by neutrophils and monocytes. BLSOmp31/ISPA is a safe and effective vaccine against B. ovis in the mouse model.